ISLAMIC RELIGIOUS EDUCATION IN THE AGE OF AI: A LITERATURE-BASED ANALYSIS OF CHALLENGES AND OPPORTUNITIES IN SHAPING STUDENTS’ ISLAMIC CHARACTER IN THE DIGITAL ERA - Rahmat Saputra (STAI Darul Qalam Tangerang, 2025)
This study analyzes relevant literature to examine the challenges and opportunities arising from the development of Artificial Intelligence (AI) on the formation of students' Islamic character in the digital era. Through a systematic literature review, this article explores how AI influences students' understanding of Islamic concepts, worship practices, and moral and ethical values. This research uses a qualitative approach by collecting and analyzing scientific articles, journals, and related publications. The results of the analysis show that AI offers wider access to religious information, but it also poses a risk of disinformation. The use of technology in worship practices opens up new opportunities, but also challenges solemnity. Additionally, AI affects students' social interactions, posing challenges such as cyberbullying. This article emphasizes the importance of digital literacy and strong character education to equip students to face the AI era. The conclusion of this study provides practical implications for PAI teachers and policymakers in designing learning strategies that are effective and relevant to the times.